OBSERVATIONS ON THE PRAWN FISHERY OF THE MANDAPAM AREA - Nandakumar, G (Indian Journal of Fisheries, 2011)
Trawling for prawns is carried out at night. The prawn fishery showedannual fluctuations and the average annual prawn catch was estimrjted to be 309.12tonnes forminig M.lWc of the trEwl landdngs. January to May was the peakseason for the fishery contributing 60.6% of the prawn catoh. The average catchper unit for prawns was 27.12 kg. The fishery was chiefly supported by Pemteiissemisulcatus (88.72%) rnd Metapenaeus affinis (11.28%).